Nation (Transnationality), Gender and Politics in the Feminist Work of Julka Chlapec-Đorđević (Knjiženstvo, časopis za studije književnosti, roda i kulture, 2023)
The topic of the article is the national discourse in the literary texts and feminist thought of the Serbian philosopher, feminist, and writer Julka Chlapec-Djordjević (1882–1969) regarding her Serbian and Czech identity, in the context of her cosmopolitan ideas and in the context of her “Prague period” of writing (1922–1945). She was of Serbian origin, but nevertheless for most of her writing career she lived in democratic Prague and participated in open Czech society before the Second World War. In that time and place, she – already in her forties – became an outspoken feminist and a writer. In Prague she also became a mediator between different cultures: “ex-Austrian”, Czech, and Serbian. This study examines her interactions with the social, political, and literary movements of the two different countries. In her remarks I emphasize how she was very familiar with Czech and Serbian culture, history, and literature – and also that of Europe and America.From her writing, I could infer that she was a Serbian patriot who lived in Prague and had a Serbian and Czech identity. On the other hand, in her texts she was a passionate and subversive intellectual: a “person of letters”, a nomadic and transnational intellectual with a great knowledge of philosophy, sociology, and also culture and literature of the globalised (in every sense of the word) world.
Keywords: Julka Chlapec-Djordjević; feminism; Central Europe; national identity; literature; Prague